2018
DOI: 10.1364/prj.6.000579
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary characteristics for one-dimensional parity-time-symmetric periodic ring optical waveguide networks

Abstract: In this paper, we design a one-dimensional (1D) parity-time-symmetric periodic ring optical waveguide network (PTSPROWN) and investigate its extraordinary optical characteristics. It is found that quite different from traditional vacuum/dielectric optical waveguide networks, 1D PTSPROWN cannot produce a photonic ordinary propagation mode, but can generate simultaneously two kinds of photonic nonpropagation modes: attenuation propagation mode and gain propagation mode. It creates neither passband nor stopband a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…We call Equation the network equation for the 1D two‐material waveguide network. One can calculate the transmissivity, reflectivity, and photonic localization in our model using the network equation with the generalized eigenfunction method.…”
Section: Model and Methodsmentioning
confidence: 99%
“…We call Equation the network equation for the 1D two‐material waveguide network. One can calculate the transmissivity, reflectivity, and photonic localization in our model using the network equation with the generalized eigenfunction method.…”
Section: Model and Methodsmentioning
confidence: 99%
“…[ 5 ] constructed PT‐symmetric optical systems with complex refractive index materials under paraxial approximation condition, which followed n(x)=n(x)$n(x)=n^{*}(x)$ distribution. Subsequently, the special optical characteristics of PT‐symmetric optical systems, [ 5–25 ] such as unidirectional invisibility, [ 10–16,20,22 ] ultrastrong transmission and reflection, [ 11,15,19 ] and coherent perfect absorption, [ 8,16,21 ] have attracted widespread attention. In, 2017, our research group [ 18 ] combined the concept of PT‐symmetry with optical waveguide networks to construct PT‐symmetric optical waveguide networks.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the singular optical properties of EM waves when propagating in these networks were studied, such as photon modes, ultrastrong extraordinary transmission and reflection, and photonic band gap. Further research [19][20][21][22][23] showed that when EM waves propagate in networks with different PT-symmetric substructures, the singular features are significantly different from each other. Identifying the causes for these differences is an interesting problem in the study of PT-symmetry systems.…”
Section: Introductionmentioning
confidence: 99%
“…This artificial optical system has also aroused great interest [15][16][17][18][19][20] due to several extraordinary phenomena such as flat broadband light transport, [16] chiral mode conversion, [17] and ultra-strong transmission and reflection, [18] non-Hermitian particle-hole symmetry, [15,19] coherent switch. [20] In 1998, optical waveguide networks [21][22][23][24][25][26][27][28][29][30][31][32][33][34] were proposed as a new kind of photonic bandgap (PBG) structure. Compared with photonic crystals, it exhibits excellent characteristics such as higher flexibility in structural symmetry, [21,23,24] and great convenience in measuring the phase and amplitude of EM waves.…”
Section: Introductionmentioning
confidence: 99%
“…[21,23] Consequently, several interesting optical features and phenomena have been demonstrated in waveguide networks, such as extremely wide PBG, [24,25] comb-like optical transmission spectrum, [27,28] and ultra-strong photonic localization. [32,33] So far, there has been no report that involves a combination of optical waveguide network and anti-PT symmetry. The PT -symmetric optical waveguide network is composed of ma-terials whose imaginary parts of refractive indices are positive and negative simultaneously.…”
Section: Introductionmentioning
confidence: 99%